MiR-335 Regulates Hif-1α to Reduce Cell Death in Both Mouse Cell Line and Rat Ischemic Models - Liu, Fu Jia (PLoS One, 2015)
Hypoxia inducible factor-1α facilitates cellular adaptation to hypoxic conditions. Hence its tight regulation is crucial in hypoxia related diseases such as cerebral ischemia. Changes in hypoxia inducible factor-1α expression upon cerebral ischemia influence the expression of its downstream genes which eventually determines the extent of cellular damage. MicroRNAs are endogenous regulators of gene expression that have rapidly emerged as promising therapeutic targets in several diseases. In this study, we have identified miR-335 as a direct regulator of hypoxia inducible factor-1α and as a potential therapeutic target in cerebral ischemia. MiR-335 and hypoxia inducible factor-1α mRNA showed an inverse expression profile, both in vivo and in vitro ischemic conditions. Given the biphasic nature of hypoxia inducible factor-1α expression during cerebral ischemia, miR-335 mimic was found to reduce infarct volume in the early time (immediately after middle cerebral artery occlusion) of embolic stroke animal models while the miR-335 inhibitor appears to be beneficial at the late time of stroke (24 hrs after middle cerebral artery occlusion). Modulation of hypoxia inducible factor-1α expression by miR-335 also influenced the expression of crucial genes implicated in neurovascular permeability, cell death and maintenance of the blood brain barrier. These concerted effects, resulting in a reduction in infarct volume bring about a beneficial outcome in ischemic stroke.